Surface Tension of Dialkyl Carbonates + (Alkanes or 1,4- Dimethylbenzene) and 1,4-Dimethylbenzene + Alkanes Binary Mixtures at T = 308.15 K - Gayol, Ana (2013)
New experimental surface tension data are reported for binary mixtures of dimethyl carbonate and diethyl carbonate with octane, decane, and 1,4-dimethylbenzene and 1,4-dimethylbenzene with octane and decane at 308.15 K and atmospheric pressure. These experimental results are compared with those reported in the literature at different temperature when they are available. The experimental results show that surface tension of these compounds depends systematically on temperature. The surface tension deviation calculated was fitted by the Redlich−Kister polynomial equation. The adjustable parameters obtained for each system are reported with the standard deviations between experimental and calculated values.